Perceived stigma and self-stigma of problem gambling: perspectives of people with gambling problems. Issue 1 (2nd January 2016) - Hing, Nerilee; Nuske, Elaine; Gainsbury, Sally M.; Russell, Alex M.T.
Abstract: Minimal research has investigated the stigma associated with problem gambling, despite its major hindrance to help-seeking and recovery. This study explored perceived stigma and self-stigma to examine stigmatizing beliefs held, how they may be internalized, coping mechanisms, and effects on help-seeking. In-depth interviews with 44 people experiencing gambling problems were analysed using interpretive phenomenology. Results revealed an overwhelming perception that problem gambling attracts acute public stigma and is publicly viewed as caused by personal failings. Participants had serious concerns about being viewed as 'a problem gambler', fearing demeaning stereotypes, social rejection, hostile responses and devaluing behaviours. Many participants internalized perceived stigma as self-stigma, with deleterious reported effects on self-esteem, self-efficacy, perceived social worth, and mental and physical health. Deep shame was a near universal emotion and exacerbated by relapse. Secrecy was the main coping mechanism used, with perceived and self-stigma found to act as major barriers to disclosure and help-seeking. The findings can inform the development of a valid understanding and conceptualization of problem gambling stigma. This is a prerequisite for effective stigma-reduction strategies to reduce public stigma and discrimination, and to lower perceived and self-stigma and increase the use of treatment services and other interventions by people with gambling problems.